2004
DOI: 10.1175/1520-0426(2004)021<0347:uieors>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in Estimates of Reynolds Stress and TKE Production Rate Using the ADCP Variance Method

Abstract: The use of acoustic Doppler current profilers (ADCPs) to measure turbulent parameters via the variance method involves uncertainties due to instrument noise and flow-related errors in measurement. For weak flows, the uncertainty in Reynolds stress measurements arises mainly from instrument noise and is proportional to the square of the velocity standard deviation, while the uncertainty in the corresponding estimates of the rate of production of turbulent kinetic energy (TKE) is proportional to the cube of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 16 publications
5
76
0
Order By: Relevance
“…(3) (Stacey et al 1999a;Williams and Simpson 2004). This result is then adjusted by an additional parameter, on the order of 1-4, to correct for the autocorrelation of the time series (Williams and Simpson 2004). However, following Rosman et al (2008), the correlation correction was not implemented in the present study and thus the uncertainty estimates for the AF method shown represent a lower bound.…”
Section: A the Variance Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(3) (Stacey et al 1999a;Williams and Simpson 2004). This result is then adjusted by an additional parameter, on the order of 1-4, to correct for the autocorrelation of the time series (Williams and Simpson 2004). However, following Rosman et al (2008), the correlation correction was not implemented in the present study and thus the uncertainty estimates for the AF method shown represent a lower bound.…”
Section: A the Variance Methodsmentioning
confidence: 99%
“…(3) (Stacey et al 1999a;Williams and Simpson 2004). This result is then adjusted by an additional parameter, on the order of 1-4, to correct for the autocorrelation of the time series (Williams and Simpson 2004).…”
Section: A the Variance Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in section 2.3, a method for calculating the variance of the estimates directly from the data is presented using the work of Williams and Simpson [26]. The conclusion is that the ADCP can provide approximate estimates of the Reynolds stess when there is minimal beam tilt, or when the wave-induced velocities are not energetic.…”
Section: Reynolds Stress Using An Adcp In An Energetic Ocean Statementioning
confidence: 99%